2015
DOI: 10.1007/s10439-015-1423-3
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Wearable Head Impact Sensors

Abstract: Inertial sensors are commonly used to measure human head motion.(R1–3) Some sensors have been tested with dummy or cadaver experiments with mixed results, and methods to evaluate sensors in vivo are lacking. Here we present an in vivo(R3–10) method using high speed video to test teeth-mounted (mouthguard), soft tissue-mounted (skin patch), and headgear-mounted (skull cap) sensors during 6–13g(R1–20) sagittal soccer head impacts. Sensor coupling to the skull (R1–3) was quantified by displacement from an ear-can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
250
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(261 citation statements)
references
References 25 publications
8
250
3
Order By: Relevance
“…The positioning of the XPatch over the mastoid process was important to ensure that the sensor was not activated by enhanced soft-tissue effects when impacts occurred. 38 The XPatch contained a low-power, high-g, triaxial accelerometer with 200g maximum per axis and a triaxial angular rate gyroscope that was used to capture 6 degrees of freedom for the linear and rotational accelerations over time of the head's center of gravity for all impacts that occurred during match participation. The time history incorporated 3 axes (x, y, z) of acceleration and 3 axes of velocity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positioning of the XPatch over the mastoid process was important to ensure that the sensor was not activated by enhanced soft-tissue effects when impacts occurred. 38 The XPatch contained a low-power, high-g, triaxial accelerometer with 200g maximum per axis and a triaxial angular rate gyroscope that was used to capture 6 degrees of freedom for the linear and rotational accelerations over time of the head's center of gravity for all impacts that occurred during match participation. The time history incorporated 3 axes (x, y, z) of acceleration and 3 axes of velocity.…”
Section: Methodsmentioning
confidence: 99%
“…The XPatch has a strong correlation with peak linear acceleration (PLA; r 2 = 0.93) 38 with a normalized root square error of 18%, but may overpredict PLA and peak rotational acceleration (PRA) by 15g ± 7g and 2500 ± 1200 rad/sec 2 , respectively. Nevins et al 30 reported that the XPatch had good agreement with PLA but underestimated PRA by more than 25%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…117 These differences may invariably influence the results of the published studies as, although some studies report the linear threshold as 14.4g, they may actually be recording from 10g…”
Section: Impact Thresholdmentioning
confidence: 99%
“…Accelerometer-based sensing with the device affixed to the athlete either on the cranium or in the mouth is in current use. The results of impact sensing from these technologies vary with the location and specific properties of the device tested, and in all cases respond to acceleration rather than force [8]. In addition, much of the presently available, accelerometer-based devices rely on wireless transmission of impact events, whereas the forcerecording strips reported here do not transmit data wirelessly, and provide information specific to the point of impact.…”
mentioning
confidence: 99%